2015
DOI: 10.1002/jid.3057
|View full text |Cite
|
Sign up to set email alerts
|

“No Bourgeoisie, No Democracy”? The Political Attitudes of the Kenyan Middle Class

Abstract: Barrington Moore's famous line 'no bourgeoisie, no democracy' is one of the most quoted claims in political science. But has the rise of the African middle class promoted democratic consolidation? This paper uses the case of Kenya to investigate the attitudes and behaviours of the middle class. Analysis of Afrobarometer survey data reveals that the middle class is more likely to hold prodemocratic attitudes. This suggests that Moore's argument deserves to be taken seriously, at least in some African countries,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…Cheeseman () begins to probe this issue in more detail in this issue. By illustrating that middle class Kenyans began to demonstrate strong affinities to co‐ethnic presidential candidates as the 2013 elections drew closer, he emphasizes that the relevance of a middle class consciousness can wax and wane depending on the broader context in which they are operating.…”
Section: Conclusion: New Frontiers In Middle Class Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Cheeseman () begins to probe this issue in more detail in this issue. By illustrating that middle class Kenyans began to demonstrate strong affinities to co‐ethnic presidential candidates as the 2013 elections drew closer, he emphasizes that the relevance of a middle class consciousness can wax and wane depending on the broader context in which they are operating.…”
Section: Conclusion: New Frontiers In Middle Class Analysismentioning
confidence: 99%
“…If one is concerned with the consumption patterns of the middle class, an absolute income or expenditure measure may be most appropriate, as chosen by Tschirley et al (2015). If one is most interested in the political activism and democratic values of the middle class, as chosen by Cheeseman (2015), Mattes (2015) and Resnick (2015), combining income or asset metrics with those incorporating educational attainment and employment status appears more fitting.…”
Section: Overview Of Special Issue Contributionsmentioning
confidence: 99%
“…As Bratton et al have argued, based on Afrobarometer survey data from 18 countries, "would-be voters in Africa consider policy performance, especially the government's perceived handling of unemployment, inflation, and income distribution". 20 Further survey research has found that the kind of voters most likely to vote on the basis of performance and the public good are those who live in urban areas, 21 are more educated, 22 and come from families that have experienced inter-ethnic marriage. 23 If this is correct, the proportion of the electorate voting on the basis of the government's record will grow in the future as levels of urbanization and education on the continent increase.…”
Section: Economic Difficulties and Assertive Votersmentioning
confidence: 99%
“…SeeMoore (1967); Lijphart (1969) refers in in seminal work on sub-cultures; for Africa see:Cheeseman (2015);Van de Walle (2003).…”
mentioning
confidence: 99%